VEGETATIVE GROWTH OF CASSAVA (Manihot esculenta Crantz.) ON THE LIQUID ORGANIC FERTILIZER OF LEGUMINOSAE SPECIES AND CONCENTRATION - Usman Siswanto; Yuliana Anggraeni; Wike Oktasari; Murti Astiningrum (BPFP Universitas Bengkulu, 2023)
Cassava is one of the food crops with continous increasing demand. This study aimed to investigate the response of vegetative cassava growth to the application of different concentrations and types of liquid organic fertilizers (LOF) from Leguminosae plants. The research was conducted from February 27 to June 27, 2022, in Kembanglimus Village, Borobudur District, and arranged factorially (4x3) using a Randomized Completely Block (RCB). The first factor was the type of liquid organic fertilizer derived from Leucaena leucocephala, Mimosa pudica, and Arachis hypogaea. The second factor was the concentration of LOF, consisting of 0 mL/L, 15 mL/L, 30 mL/L, and 45 mL/L. Chlorophyll content was analyzed using spectrophotometer and protein contet of leaf and tuber were analyzed with Kjeldahl methods. The results demonstrated that type of LOI did not have a significant effect on all parameters. Liquid organic fertilizer from Leguminosae plants with 0 mL/L concentration resulted in the highest number of roots. Type of liquid organic fertilizer from Leucaena leaf with a concentration of 24.95 mL/L gave the highest number of roots, while type of LOF of Mimosa pudica with a concentration of 26.31 mL/L gave the highest number of branches. Type of liquid organic fertilizer of Arachis hypogaea with a concentration of 45 mL/L resulted in the highest total chlorophyll content, leaf protein content, and protein content in the tubers